2000
DOI: 10.1038/35023008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oncogenic mutations in Smoothened and Patched can be reversed by cyclopamine

Abstract: Basal cell carcinoma, medulloblastoma, rhabdomyosarcoma and other human tumours are associated with mutations that activate the proto-oncogene Smoothened (SMO) or that inactivate the tumour suppressor Patched (PTCH). Smoothened and Patched mediate the cellular response to the Hedgehog (Hh) secreted protein signal, and oncogenic mutations affecting these proteins cause excess activity of the Hh response pathway. Here we show that the plant-derived teratogen cyclopamine, which inhibits the Hh response, is a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
1,156
4
11

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,215 publications
(1,209 citation statements)
references
References 26 publications
38
1,156
4
11
Order By: Relevance
“…We speculated that Fbxl17 could mediate the release by promoting Sufu polyubiquitylation and degradation. To assess the latter, we analyzed Sufu protein levels in mouse embryonic fibroblasts (MEFs) that express the receptor Ptch1 ( Ptch1 +/+ ), MEFs with heterozygous loss of Ptch1 ( Ptch1 +/− ), and MEFs deficient in Ptch1 ( Ptch1 −/− ), which have constitutive Hh signaling (Taipale et al , 2000). Strikingly, MEFs Ptch1 −/− and Ptch1 +/− cells showed a decrease in Sufu levels corresponding to the degree of Ptch loss and the consequent Hh activation.…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that Fbxl17 could mediate the release by promoting Sufu polyubiquitylation and degradation. To assess the latter, we analyzed Sufu protein levels in mouse embryonic fibroblasts (MEFs) that express the receptor Ptch1 ( Ptch1 +/+ ), MEFs with heterozygous loss of Ptch1 ( Ptch1 +/− ), and MEFs deficient in Ptch1 ( Ptch1 −/− ), which have constitutive Hh signaling (Taipale et al , 2000). Strikingly, MEFs Ptch1 −/− and Ptch1 +/− cells showed a decrease in Sufu levels corresponding to the degree of Ptch loss and the consequent Hh activation.…”
Section: Resultsmentioning
confidence: 99%
“…20 Cyclopamine treatments were carried out using DMEM-F12 (Invitrogen, Paisley, UK) supplemented with 2% FBS, and the doses were previously described. 14,21 Cells (2 ϫ 10 6 /flask) were seeded in triplicate flasks and allowed to grow to approximately 50% confluence prior to treatment. Cells were treated for 48 hr and trypsinized for counting and analysis.…”
Section: Treatment With Cyclopaminementioning
confidence: 99%
“…12,13 Sheep grazing on this lily showed a high proportion of birth defects associated with disrupted Hh signalling in their offspring, without apparent harm to the adult animals. Cyclopamine blocks the abnormal cell growth associated with oncogenic mutations of Ptch and Smo in fibroblasts, 14 inhibits the malignant growth of medulloblastoma cells lacking Ptch function 15 and inhibits the SHH-dependent growth of small-cell lung cancer cells. 16 The lack of adverse effects of cyclopamine exposure in adults thus far described makes it a possible therapeutic agent for tumours associated with deregulated Hh signalling.…”
mentioning
confidence: 99%
“…17 Other genetic alterations found in medulloblastomas, which may have prognostic predictive value are those of the N-Myc and ERRB2 oncogenes, 18 loss of caspase-8 expression, 19 and mutations of several signal transduction pathways including the PTCH1/"Sonic Hedgehog", Wingless" (WNT/WG)/ beta catenin, and PDGF-a/RAS/MAP tyrosine kinase pathways. 20,21 At this time, the best independent predictor of medulloblastoma outcome may be the overall pattern of gene expression. DNA microarray gene expression analyzed in tumor tissue from a large cohort of medulloblastoma patients showed that clinical outcome is predicted by the profile of gene expression, and is a better predictor than the expression or amplification of any single gene or any single gene mutation.…”
Section: Diagnostic/prognostic Modalitiesmentioning
confidence: 99%
“…These include imatinib mesylate (Gleevec), a PDGFa/RAS/MAP tyrosine kinase inhibitor, 21 Erlotinib (Tarceva), which inhibits the oncogene, ERBB2 tyrosine kinase, and Iressa (gefitinib), which inhibits the EGFR tyrosine kinase. 13 Moleculartargeted therapies still in pre-clinical evaluation include cyclopamine, a plant-derived teratogen that suppresses the membrane protein, SMO, which is activated and stimulates cell proliferation when there are mutations in the PTCH/Sonic Hedgehog pathway of some medulloblastomas; 20 cyclopamine has side effects that limits its clinical application, but other agents which inhibit this pathway are also under development.…”
Section: Common Pediatric Brain Tumors and Therapy Advancesmentioning
confidence: 99%